2018
DOI: 10.1021/acscatal.7b04400
|View full text |Cite
|
Sign up to set email alerts
|

A Buried Water Molecule Influences Reactivity in α-Amylase on a Subnanosecond Time Scale

Abstract: The subset of catalytically competent conformations can be significantly small in comparison with the full conformational landscape of enzyme–substrate complexes. In some enzymes, the probability of finding a reactive conformation can account for up to 4 kcal/mol of activation barrier, even when the substrate remains tightly bound. In this study, we sampled conformations of human pancreatic α-amylase with bound substrate in a molecular dynamics (MD) simulation of over 100 ns and calculated energy profiles alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(57 citation statements)
references
References 54 publications
5
52
0
Order By: Relevance
“…changing the rotamer state of a single active site residue -by raising the transition state barrier via an unfavorable electric field fluctuation on longer timescales to promote other functional states in the enzyme cycle, for example, substrate binding or product release. These findings are also consistent with a gating mechanism whereby the reaction can proceed at specific conformations where the key residue(s), in this case the Asp-103 residue, are optimally positioned 42 . This is likely one problem in enzyme design where often the active site is "overdesigned", for example the assumption that the role of Asp-103 is to stabilize the oxyanion hole, and thus fails to incorporate productive coupled motions on different timescales that supports the enzyme turnover cycle 43 .…”
supporting
confidence: 82%
“…changing the rotamer state of a single active site residue -by raising the transition state barrier via an unfavorable electric field fluctuation on longer timescales to promote other functional states in the enzyme cycle, for example, substrate binding or product release. These findings are also consistent with a gating mechanism whereby the reaction can proceed at specific conformations where the key residue(s), in this case the Asp-103 residue, are optimally positioned 42 . This is likely one problem in enzyme design where often the active site is "overdesigned", for example the assumption that the role of Asp-103 is to stabilize the oxyanion hole, and thus fails to incorporate productive coupled motions on different timescales that supports the enzyme turnover cycle 43 .…”
supporting
confidence: 82%
“…This strong dependence of the reactivity on specic enzyme conformations has been demonstrated by different computational studies, in which the activation barriers were calculated for several different initial conformations of the same enzyme. [7][8][9][10][11][12][13][14][15][16] For example, in ketosteroid isomerase, the barriers change is about 20 kcal mol À1 due to a structural variation on the active site, which determines its closure and, consequently, the progress of the catalyzed reaction. 12 In uoroacetate dehalogenase, twenty snapshots in three different systems were used, and it was found that the barrier of each reaction varies by up to 15 kcal mol À1 .…”
Section: The Inuence Of Enzyme Conformations On Reactivitymentioning
confidence: 99%
“…The uctuations in the barrier were caused, to a very signicant extent, by the uctuations in the position and orientation of this water molecule and of the two active-site reactive residues. 7 These are only a few of a number of studies in which this phenomenon was studied in detail. Combining all these barriers into a single, observed one is a matter of intense research.…”
Section: The Inuence Of Enzyme Conformations On Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The CAM-B3LYP functional [36] performed amongst the best DFT functionals in geometry optimizations in previous benchmarking studies [37] and B3LYP [38] has been successfully employed to describe the energetics of general enzymatic mechanisms using QM/MM. [39] To study the reaction mechanism, linear transit scans were conducted along the appropriate reaction coordinates to obtain adequate conformations to use as guesses for the free optimization of the transition states (TS). The nature of the TSs was confirmed through the calculation of the vibrational frequencies, having just one imaginary frequency.…”
Section: Qm/mm Calculationsmentioning
confidence: 99%